Perkosaan anak perempuan: Pelaku dan pola kejadian - Karnaji Karnaji (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Rape to girls is categorized as violence that continuously happened. This research looks at the sexual harrasement phenomena from the perpetrator’s point of view. Many cases indicate that the subject often has close connection with the victims such as neighbour, relative, teacher, grandfather, father, or even young underage male surrounding the victims. It means that both victims and the subjects are psychologically immature but for several reasons they have to involve in a situation which destruct their future. Therefore, there is a need to frame various factors that drive the subject for doing sexual harrasement. By using materials on the newspaper, this research employs qualitative-descriptive method that purposively uses Jawa Pos news as single resource of the data. The result shows that particular places affect the subject in conducting their action. There are four places that are usually used as a site of sexual harrasement. First is in the area that is hidden and safe from observations of the surrounding environment, especially in the victim's home. Second, other areas prone to the occurrence of acts of rape are zones completely open and away from the reach of community control, such as on the streets, in public places, in a quiet courtyard, at the cemetery, and so on. Third, the place is usually chosen to rape, one of them is in school. Fourth, in the region in the eyes of the public is viewed as an area of